تكملةُ فتح الملهم بشرحِ صحيح مسلم: نُبذةٌ عن حياة مؤلفه، ومنهجه ، وميزاتِه و المقارنة بينه وبين فتح الملهم و الشروح الأخرٰى: Takmilah Fatḥ al-Mulhim bi Sharḥ Ṣaḥīḥ Muslim: A Brief History of the Author’s Life, Methodology and Attributes and a Comparison between Fatḥ al-Mulhim and other Commentaries” - Amin Ullah (MEI, 2024)
The Tradition (Sunnah) of the messenger of Allah (peace and blessings be upon him) is the second source of Islamic text after the Holy Quran. It is both a theoretical elucidation and practical application of the Holy Quran as Allah mentions in the Quran, “(We sent them) with clear signs and scriptures. And We sent down the Reminder (The Qur’ān) to you, so that you explain to the people what has been revealed for them, and so that they may ponder.” [Quran 16:44]. Allah, the Exalted, has prepared, in every time and place, men who serve the Sunnah in various ways, like preserving it, protecting it, refuting allegations against it, repelling doubts from it, categorizing its books, discussing its narrators, examining its chains of narrators, explaining its texts, propagating its call and message and teaching the truths of its creed, the secrets of its jurisprudence, the nobility of its morals and the beauty of its ethics. Scholars of the Indian subcontinent, which today includes India, Pakistan and Bangladesh, have contributed significantly to serving the Sunnah; in researching it, verifying the narrations, adding marginalia, explaining and spreading it. It is well-known and accepted by the scholars of this Ummah that the Ṣaḥīḥ or Imām Bukhārī and the Ṣaḥīḥ or Imām Muslim are among the greatest of the books of Sunnah and the most authentic of Islamic texts after the Quran. Each has advantageous attributes and special characteristics that the People of Knowledge and experts of Ḥadīth are aware of. The scholars of the Sunnah have served these two books as they have served other books. They have written commentaries that clarify that difficult texts and explain the ambiguities. Among the commentaries of Ṣaḥīḥ Muslim is Fatḥ al-Mulhim bi Sharḥ Ṣaḥīḥ Muslim written by the erudite scholar, Shabbīr Aḥmad al-ʿUthmānī for whom Allah decreed the end of his life before he could complete this work. He was able to complete his commentary until The Book on Marriage (Kitāb an-Nikāḥ). A great scholar who comes from a family of people of knowledge and virtue (some of whom are descendants of others) was granted the honor of completing this work. That scholar was the jurist, the erudite, Shaykh Muḥammad Taqī al-ʿUthmānī son of the jurist, the erudite, Muftī Muḥammad Shafīʿ, may Allah have mercy on him, reward him abundantly and accept him among the pious. The Shaykh and Muftī has fulfilled the rights of these narrations, explained them comprehensively, included contemporary discussions and issues and provided solutions under the guiding light of the Pure Islamic Law. Moreover, he responded to criticisms that contemporaries had excused themselves from with undeniable proofs in clear and uncomplicated language. This discussion titled “Takmilah Fatḥ al-Mulhim bi Sharḥ Ṣaḥīḥ Muslim: A Brief History of the Author’s Life, Methodology and Attributes and a Comparison between Fatḥ al-Mulhim and other Commentaries” aims to introduce this commentary and to mention a brief history of the life of the esteemed author, his methodology in his commentary, his attributes and to compare between this work with other commentaries on Ṣaḥīḥ Muslim. In the end, we pray to Allah that he accepts from the Muftī his beautiful efforts and that He rewards him knowledge, understanding and Sunnah the best of which is rewarded to honest scholars and that He makes us and him among those who learn then practice, practice then have sincerity and have sincerity then are accepted.